Buku Ensiklopedia Motif Songket Palembang Sebagai Media Pelestarian Kearifan Lokal Bagi Generasi Muda - Muhammad Ibrahim Daud; Husni Mubarat; Didiek Prasetya (VisArt: Jurnal Seni Rupa dan Design, 2026)
Palembang songket is one of Indonesia’s cultural heritages that holds significant historical, aesthetic, and philosophical values. However, amid globalization and the rapid growth of popular culture, young people’s interest in local culture, including Palembang songket, has gradually declined. The design of the Palembang Songket Motif Encyclopedia aims to present a visual information medium that introduces, documents, and preserves Palembang songket motifs in an educational and engaging way, particularly for the younger generation. The design process applies a visual communication design approach by adapting Palembang songket motifs as the main visual identity. The Umpak Pangkal motif was selected as the big idea due to its philosophical meaning as a foundation and an introduction, which aligns with the function of an encyclopedia as an initial gateway to knowledge. The encyclopedia content includes a brief history of Palembang songket, classifications of motifs, ornamental structures, and symbolic color meanings derived from the traditional motif color nomenclature. The final outcome consists of the main medium in the form of an encyclopedia book, supported by promotional and follow-up media such as posters, x-banners, calendars, wall clocks, ID cards, and merchandise. This design is expected not only to serve as an informational medium but also as a cultural education and appreciation tool that enhances public awareness of the cultural values of Palembang songket while presenting tradition in a visually modern and relevant manner